Professionally oriented environment as a condition for formation of specialists’ competence (in the context of training of television reporters) - Lisnevska, А. (Continuing Professional Education: Theory and Practice, 2019)
Strengthening of cognitive and informational foundations in the modern world are not covered by the traditional concept of professional qualification, so the concept of competence becomes more adequate. The article deals with professionally oriented environment as a pedagogical condition for formation of future specialists’ competence and provides rationale for its creation in the process of training of television reporters. One of the components of future specialists’ competence is professional thinking. It should be formed in a specially organized learning environment filled with meaningful professionally oriented content meeting the requirements of professional training. Professionally-oriented environment has a task-oriented nature (formation of professional competence and thinking) based on the development and implementation of active forms and methods of learning into the training process. In this case the role of the teacher changes from the information source to students’ assistant and sometimes co-author within the learning process. The specific forms of training of future television reporters at the university are considered as an example of the use of active training methods in the space of a professionally-oriented environment: problem solving lecture, practical seminar, lecture-discussion.